Efficacy of commercial products on nursery pig growth performance fed diets with fumonisin contaminated corn. Issue 4 (21st November 2020) - Rao, Zhong-Xing; Tokach, Mike D; Dritz, Steve S; Woodworth, Jason C; DeRouchey, Joel M; Goodband, Robert D; Calderon, Hilda I
Abstract: Two experiments were conducted to determine the efficacy of various commercial products on growth performance of nursery pigs fed diets high in fumonisin. In experiment 1, 350 pigs (241 × 600; DNA, Columbus, NE; initially 9.9 kg) were used with five pigs per pen and 14 replicates per treatment. After weaning, pigs were fed common diets for 21 d before the experiment started. The five dietary treatments consisted of a positive control (low fumonisin), a negative control (60 mg/kg of fumonisin B1 + B2 in complete diet), and the negative control with one of three products (0.3% of Kallsil Dry, Kemin Industries Inc., Des Moines, IA; 0.3% of Feed Aid Wide Spectrum, NutriQuest, Mason City, IA; 0.17% of Biofix Select Pro, Biomin America Inc., Overland Park, KS). Diets were fed in mash form for 14 d and followed with a low fumonisin diet for 13 d. For the 14-d treatment period, pigs fed the positive control diet and Biofix Select Pro had greater ( P < 0.05) average daily gain (ADG), average daily feed intake (ADFI), and gain:feed (G:F) compared to those fed the high fumonisin negative control, or high fumonisin diets with Kallsil Dry or Feed Aid Wide Spectrum. Serum sphinganine to sphingosine ratios (SA:SO) were greater ( P < 0.05) in all pigs fed high fumonisin diets compared to the positive control. In experiment 2, 300 pigs (241 × 600; DNA; initially 10.4 kg) were used. Procedures were similar to experiment 1 except there were 12 replicate pens per treatment, high fumonisin diets contained 30 mg/kg fumonisin, and experimental diets were fed for 28 d. Similar to experiment 1, pigs fed the positive control diet and treatment with Biofix Select Pro had greater ( P < 0.05) ADG and G:F, and lower ( P < 0.05) serum SA:SO compared to pigs fed the high fumonisin negative control, or high fumonisin diets with Kallsil Dry or Feed Aid Wide Spectrum. In summary, pigs fed diets containing 60 mg/kg of fumonisin for 14 d or 30 mg/kg of fumonisin for 28 d had poorer ADG and G:F and greater serum SA:SO compared to pigs fed a diet with less than 5 mg/kg of fumonisin. Adding Biofix Select Pro to diets appeared to mitigate the negative effects of high fumonisin concentrations, while Kallsil Dry and Feed Aid Wide Spectrum did not.